Magnetostatic pressure as a factor of spiral domain stabilization in ferrite-garnet films - Mamalui, Ju.A.; Siryuk, Ju.A. (Functional Materials, 2008)
Stable spiral domains (SpD) surrounded by bubble lattice (LED) and existing in the absence of magnetic fields have been experimentally studied in epitaxial ferrite-garnet films. Thermodynamic approach and the concept of magnetostatic pressure are used to explain the SpD behavior with bias field (H) and temperature (T) change. It is shown that T- or H-induced phase transitions (PT) in LED initiate PT in SpD.